Black markets: Fascist constructions of race in East African marketplace newsreels. Issue 1 (February 2021) - Garvin, Diana
This article investigates East African marketplace films to trace the developmental arc and varieties of Italian Fascist racism in empire. Totalling over 70 in number, these bantam adventures in souks and bazaars were among the most popular formats for 1930s newsreels purporting to document daily life in the colonies. The short documentary-style films were produced by LUCE, the cinematic arm for state-run propagandistic projects. Like many of the films produced by this larger cinematic body, marketplace newsreels cast Italian technology in starring roles. Tractors and sewing machines frame Italian as modernizing heroes. By focusing on visual and acoustic examples, the article examines the markets of propaganda through a sensory focus. Ultimately, this approach intertwines two modes of inquiry: the history of East African architecture and urbanism, and Fascist Italian empire film.